2020
DOI: 10.1016/j.resp.2019.103305
|View full text |Cite
|
Sign up to set email alerts
|

Mid-cervical interneuron networks following high cervical spinal cord injury

Abstract: Spinal interneuron (IN) networks can facilitate respiratory motor recovery after spinal cord injury (SCI). We hypothesized that excitatory synaptic connectivity between INs located immediately caudal to unilateral cervical SCI would be most prevalent in a contra-to ipsilateral direction. Adult rats were studied following chronic C2 spinal cord hemisection (C2Hx) injury. Rats were anesthetized and ventilated and a multi-electrode array was used to simultaneously record INs on both sides of the C4-5 spinal cord.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Subsequent studies by the Edgerton group showed that interneurons not only contributed spontaneously to plasticity after injury, but they could also be therapeutically harnessed to improve outcome after partial SCI. This was also more recently shown within respiratory networks (Darlot et al, 2012), where chemogenetic (Satkunendrarajah et al, 2018) or neurochemical (Streeter et al, 2020) stimulation of SpINs can modulate and even improve functional output after SCI. Engineering and transplantation of subsets of SpINs have also been shown to enhance plasticity and functional recovery after SCI (White et al, 2010;Brock et al, 2018;Dulin et al, 2018;Kumamaru et al, 2018;Zholudeva et al, 2018b).…”
Section: Ongoing Research Perspectivessupporting
confidence: 54%
“…Subsequent studies by the Edgerton group showed that interneurons not only contributed spontaneously to plasticity after injury, but they could also be therapeutically harnessed to improve outcome after partial SCI. This was also more recently shown within respiratory networks (Darlot et al, 2012), where chemogenetic (Satkunendrarajah et al, 2018) or neurochemical (Streeter et al, 2020) stimulation of SpINs can modulate and even improve functional output after SCI. Engineering and transplantation of subsets of SpINs have also been shown to enhance plasticity and functional recovery after SCI (White et al, 2010;Brock et al, 2018;Dulin et al, 2018;Kumamaru et al, 2018;Zholudeva et al, 2018b).…”
Section: Ongoing Research Perspectivessupporting
confidence: 54%
“…Hemisection of the cervical level 2 (C2) spinal cord from the midline to lateral edge has been used extensively to study respiratory plasticity following SCI ( Bezdudnaya et al, 2017 ; Mantilla et al, 2017 ; Streeter et al, 2020 ). C2 hemisection axotomizes descending bulbospinal pathways originating in the rVRG of the medulla, thereby interrupting their connections to the PhMNs located at cervical levels C3-C5.…”
Section: Resultsmentioning
confidence: 99%
“…Interneuronal (Lane, 2011;Lane et al, 2009;Sandhu et al, 2009) pathways near the phrenic motor nucleus have been suggested to play an important role in respiratory neuroplasticity after spinal cord injury. Additionally, these interneurons may modulate the activity of respiratory motoneurons normally or during conditions of altered respiratory drive (Kirkwood et al, 1993;Streeter et al, 2017;Streeter et al, 2020).…”
Section: Discussionmentioning
confidence: 99%